The Nordic models in political science - Boutsen, Frank R.; Knutsen, Oddbjørn; Dvorak, Justin D. (San Diego c)
"The Nordic countries - Denmark, Finland, Iceland, Norway and Sweden - are frequently considered a distinct group of countries in political science studies. The term Nordic model(s) is sometimes used to describe the policies pursued by these countries. The aim of the book is to examine whether there is one or several Nordic model(s), whether there have been any changes over time in the distinctiveness of the Nordic countries, and when and why the Nordic model(s) emerged. Moreover, in light of recent global economic, legislative and political integration, will the Nordic distinctiveness last? This book examines Nordic models in several key areas of political science, such as state- and nation-building, political parties and party systems, determinants of party choice, representation and parliamentarism, gender and politics, central governmental institutions, regional and local governments, interest intermediation and interest group representation, and welfare state and knowledge regimes."
Keywords: Audiology